Accuracy of Different Shoulder Scan Examination for Diagnosis of Rotator Cuff Pathologies: A Systematic and Meta-Analysis Review - Alsufyani, Emad Ruddah; Ahmad, Tayyab; Almalki, Meshari Musaad; Alsalmi, Ahmed Atiah (International Journal of Innovative Research in Medical Science, 2022)
Objectives: we aimed to compare the diagnosis accuracy between US and MRI in the diagnosis of full-thickness and partial-thickness rotator cuff tears and biceps tendon tears with arthroscopy used as the reference standard. Methodology: Comprehensive electronic search with time and language restrictions was conducted. Several known databases were included Ex: “PubMed, The Cochrane Library, Web of Science” from 2020 to 2020. We combined the search terms and limited the study to the English language. Depending on PRISMA checklist we would remove duplicates, articles would be screened based on title, abstract, and full text. Results: The electronic search strategy conducted in this review ended in 875 hits which after removing of duplicated reduced to 360 studies. These 360 studies were considered eligible for further evaluation, from which 348 studies were excluded for different reasons as 245 studies based on title and abstract, 86 studies do not relevant to the subject of this study or sitting of this review, 17 consider replies of authors, 2 books, and 28 were reviews. At end, 12 articles were included in the qualitative synthesis of the present review. Conclusion: we found that MRI had slightly better superiority than its accuracy, sensitivity and specificity especially, in Full and intact rotator cuff injuries. However, according to previous studies the use of US is still good because of its good sensitivity and specificity and cost- effective approach.